Comparison of HTC Vive™ Virtual Reality Headset Position Measures to Center of Pressure Measures. (November 2019) - Sylcott, Brian; Williams, Keith; Hinderaker, Mark; Lin, Chia-Cheng
This study was completed to validate a virtual reality (VR) headset (HTC Vive TM, Taiwan) as a tool to measure postural sway using the position and orientation tracking capabilities built into the VR system. If validated, the headset could be a cost-effective tool for balance assessments. Unity was used to develop an optical flow environment for VR. Study participants were able to experience three different speeds of optical flow displayed through the HTC Vive headset. However, for this study, participants were shown a scene in the virtual environment that did not move, causing no optical flow for the participant. A force plate and VR headset recorded position measurements during each trial. The Pearson correlation coefficients between the headset and the force plate data measurements were calculated in MATLAB, along with the root-mean-squared and peak-to-peak values for each trial. Results show that correlations in the AP plane tended to be greater than 0.4 and correlation in the ML plane tended to be greater than 0.6. The VR headset may be used for postural control measurements in clinic. However, further development of software and testing protocols for balance assessments is needed.